An Equivalent Circuit Model for Lithium Battery of Electric Vehicle considering Self-Healing Characteristic - Zhaodi Pei; Xiaoxu Zhao; Huimei Yuan; Zhen Peng; Lifeng Wu (Journal of Control Science and Engineering)
Considering the self-healing phenomenon of lithium batteries during intermittent discharge, a self-healing characteristic-based equivalent circuit model of lithium batteries is proposed. The mathematical description of the lithium battery in the self-healing process is obtained through the analysis of the equivalent circuit model. Based on experimental platform, an experiment considering self-healing characteristic was performed. Result shows that the self-healing characteristic-based lithium battery equivalent circuit model can describe the voltage of the lithium battery accurately during the self-healing process.